Persistent post-surgical pain following breast cancer surgery: an observational study in a tertiary care hospital - Siddiqui, Ali Sarfraz; Sana Zeeshan; Aliya Ahmed; Shaista Khan; Admin (Journal of the Pakistan Medical Association, 2020)
Abstract Introduction: Persistent post-surgical pain (PPSP) is significant issue following breast cancer treatment that leads to disability and psychological distress and is often difficult to manage. Objectives: Primary objective of this study was to determine the frequency of persistent pain in patients after breast cancer surgery while the secondary objective was to see the distribution and characteristics of pain in these patients. Methods: In this prospective observational single cohort study all adult female patients with biopsy proven carcinoma of breast who were scheduled for elective definitive breast cancer surgery from 1st August 2016 to 31st January 2017 were enrolled. Total 120 patients were followed for up to three months after surgery and those who had persistent pain were followed up for six months after operation. Results: Out of the 120 patients, twenty six (21.7%) patients developed persistent post-surgical pain for up to three months while in seventeen (14.2%) patients pain continued for up to six months after operation. Of twenty six patients with PPSP, eleven (42.3%) had burning pain, ten (38.5%) had throbbing pain, three (11.5%) patients had numbness while two patients had mixed character of pain. Eleven patients developed pain at more than one site. Pain was distributed in axilla, chest wall, upper arm and surgical scar area. Fifteen out of twenty six patients (57.7%), had pain in axilla. Continuous...